Okak 1913, Eskimohäuser der Station - Bohlmann, Ernst, 1864-1945. (2001)
Photograph of Inuit houses at Okak mission station in the winter of 1913. Several dogs can be seen lying in the snow in the foreground of the picture. Photograph of Inuit houses at Okak mission station in the winter of 1913. Several dogs can be seen lying in the snow in the foreground of the picture.